Preventive examination: Knowledge and practices about the perspective of adolescents an experience report (Research, Society and Development, 2021)
Describe the lived experience of nursing students in front of an educational action carried out during a university extension. This study corresponds to an experience report of a descriptive type with a qualitative approach, based on the experiences experienced during an educational activity for adolescents carried out by a group of nursing students participating in the Health Education Extension Project - PROES of a private university center located in Maceió, Alagoas in the year 2020. The action took place at a school located in the Cidade Universitária neighborhood and was aimed at students from the 1st to the 3rd year of high school, aged between 14 and 19 years old. The theme approached was about STI's and Pap smear. Carrying out this action made it possible to share information on issues relevant to sexual and reproductive life, in addition to offering guidance on health promotion and self-care. Students were interested and participative in the activity developed. The importance of carrying out these activities is noted, as they allow the tracking and prevention of infections prevalent in this stage of life, as well as guidance on self-care, thus, it is worth highlighting the relevance of activities aimed at adolescents during the school period, showing as the real need for nursing care in this space.